2018
DOI: 10.5194/os-14-105-2018
|View full text |Cite
|
Sign up to set email alerts
|

Using kinetic energy measurements from altimetry to detect shifts in the positions of fronts in the Southern Ocean

Abstract: Abstract. A novel analysis is performed utilizing cross-track kinetic energy (CKE) computed from along-track sea surface height anomalies. The midpoint of enhanced kinetic energy averaged over 3-year periods from 1993 to 2016 is determined across the Southern Ocean and examined to detect shifts in frontal positions, based on previous observations that kinetic energy is high around fronts in the Antarctic Circumpolar Current system due to jet instabilities. It is demonstrated that although the CKE does not repr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…While the higher values in OFAM3 may suggest an overestimated variability in these eddy-rich regions, we believe that the actual biases are smaller than indicated here. Previous studies suggest systematic negative biases of SST variability represented in gridded observation-based SST analysis products 13,23,24 . Specifically, these studies report a systematic underestimate of eddy kinetic energy in the Southern Ocean by as much as 60-70% when calculated from gridded altimetry data because of interpolation, which smooths variability, compared to along-track data.…”
Section: Resultsmentioning
confidence: 97%
“…While the higher values in OFAM3 may suggest an overestimated variability in these eddy-rich regions, we believe that the actual biases are smaller than indicated here. Previous studies suggest systematic negative biases of SST variability represented in gridded observation-based SST analysis products 13,23,24 . Specifically, these studies report a systematic underestimate of eddy kinetic energy in the Southern Ocean by as much as 60-70% when calculated from gridded altimetry data because of interpolation, which smooths variability, compared to along-track data.…”
Section: Resultsmentioning
confidence: 97%
“…Accurately representing the horizontal circulation of the North Atlantic is a persistent challenge for ocean modellers. In particular, models commonly fail to simulate a Gulf Stream that separates from the North American coast at Cape Hatteras (35 • N, 75 • W) and a North Atlantic Current that flows north along the east side of the Grand Banks from 40 to 51 • N (Rossby, 1996;Chassignet and Marshall, 2008). In ACCESS-OM2 and ACCESS-OM2-025, the Gulf Stream flow is too weak and overshoots the separation latitude by about 4 • relative to observations (Fig.…”
Section: Atlantic Oceanmentioning
confidence: 99%
“…Frontal regions are also sites of pronounced exchange between the deep and surface ocean: both the upwelling (rising) of deeper waters and subduction (descending) of surface waters to the abyssal ocean is enhanced in frontal zones 16,17 . Additionally, fronts can catalyse the generation of meso-scale "eddies" 18,19 and sub-meso scale "filaments" which are able to bring nutrients from the deep ocean to the surface where they can be consumed by biological components of the system 20,21 . These details are shown schematically in Fig.…”
Section: The Physical Oceanography Of Southern Ocean Frontsmentioning
confidence: 99%
“…The primary assumption of these analyses is that if a contour SSH shifts, then its associated fronts will shift with it. However, more recent work employing "local" definitions (see section 2) has shown that this is not necessarily true, with numerous studies failing to detect any long-term trend in the position of the ACC fronts 19,25,41,42,94,95 , although there is some evidence of localized frontal movements and changes in frontal intensity 40,41 . Additionally, some recent studies provide only limited evidence of a systematic response of fronts to changing atmospheric forcing 25,35,42 .…”
Section: Observed and Projected Changes In Southern Ocean Frontsmentioning
confidence: 99%